1995
DOI: 10.1093/mnras/273.1.30
|View full text |Cite
|
Sign up to set email alerts
|

The shapes of galaxy clusters

Abstract: We have reanalyzed a data set of 99 low redshift (z < 0:1) Abell clusters studied previously by Rhee, van Haarlem & Katgert (1989), and determined their shapes. For this, three di erent measures are used: two of which were originally used by Rhee et al., and one of which was used by Plionis, Barrow & Frenk (1991) in their investigation of clusters in the Lick catalogue. We use Monte-Carlo simulations of clusters to investigate the errors in the methods. For low ellipticity, all methods overestimate the cluster… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
57
2

Year Published

1998
1998
2015
2015

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 54 publications
(67 citation statements)
references
References 40 publications
8
57
2
Order By: Relevance
“…Adami et al (1998b) have shown that enforcing circularity could create a central artificial cusp in the number density profile of the stacked cluster. However, lower mass clusters are more elongated than higher mass clusters (see Fasano et al 1993;de Theije et al 1995;Plionis et al 2004), so the effect of assuming circularity should lead to more cuspy density profiles for lower mass clusters, which is opposite to what we find. Indeed, the effect reported by Adami et al does not seem to be strong enough to account for the differences seen in the density profiles of the stacked clusters of different masses (compare Fig.…”
Section: Number Density Profiles and Projection Effectscontrasting
confidence: 99%
“…Adami et al (1998b) have shown that enforcing circularity could create a central artificial cusp in the number density profile of the stacked cluster. However, lower mass clusters are more elongated than higher mass clusters (see Fasano et al 1993;de Theije et al 1995;Plionis et al 2004), so the effect of assuming circularity should lead to more cuspy density profiles for lower mass clusters, which is opposite to what we find. Indeed, the effect reported by Adami et al does not seem to be strong enough to account for the differences seen in the density profiles of the stacked clusters of different masses (compare Fig.…”
Section: Number Density Profiles and Projection Effectscontrasting
confidence: 99%
“…the selection clusters or member galaxies. Neglecting all these differences, we find that most measurements of the shapes inferred from galaxy positions in clusters and massive groups point to a mean axial ratio of ∼(0.5−0.6) and an intrinsic scatter of ∼0.15 (Binggeli 1982;Plionis et al 1991;de Theije et al 1995;Basilakos et al 2000). Our results are fully compatible with these findings, although slightly larger mean and smaller scatter is preferred.…”
Section: Shape In Position Spacesupporting
confidence: 82%
“…An analysis of cluster ellipticities is beyond the scope of this paper, but we expect them not to be very large for the following reasons. First, our clusters are rich, and de Theije, Katgert, & van Kampen (1995) showed ellipticity to decrease significantly with increasing richness, reaching a value of $0.2 for Abell richness k80. Second, our clusters are nearby, and both Melott et al (2001) and Plionis (2002) showed cluster ellipticity to decrease with decreasing redshift, reaching $0.3 at z $ 0:05.…”
Section: Appendix C the Ensemble Cluster And Its Implied Propertiesmentioning
confidence: 74%